Avaliação da usabilidade do aplicativo CIPE-APS nas consultas de pré-natal e pós-parto - Matiolli, Amanda Pontes [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The nurse is one of the essential professionals in monitoring low-risk prenatal care. In this sense, the development of mobile devices and the adoption of new technologies are strong allies for nursing, since with the rise of information and communication technologies in health, applications have gained even greater spaces and one of the essential parameters for their assessment of quality is a usability. Objective: to evaluate the usability of the CIPE-APS application by nurses working in Primary Health Care during prenatal and postpartum consultations. Methods: This is a methodological study to assess the usability of the application. The usability assessment was carried out with 14 nurses, using a System Usability Scale (SUS), following the ISO / IEC 25010: 2011 standard. Results: The CIPE-APS application obtained positive scores for usability, being evaluated as Best imaginable (57%), Excellent (29%) and Good (14%) by survey participants. Conclusions: The CIPE-APS application has high scores on the SUS scale, assuring information for nursing consultations and for the health-disease process included in the pregnancy-puerperal cycle.

Introdução: O enfermeiro é um dos profissionais indispensáveis no acompanhamento do pré-natal de baixo risco. Nesse sentido, o desenvolvimento de dispositivos móveis e a adoção de novas tecnologias se constituem fortes aliados para o cuidado de enfermagem, visto que com a ascensão das tecnologias de informação e comunicação em saúde, os aplicativos conquistaram espaços ainda maiores e um dos parâmetros essenciais para sua avaliação da qualidade é a usabilidade. Objetivo: Avaliar a usabilidade do aplicativo CIPE-APS por enfermeiros inseridos na Atenção Primária à Saúde em consultas de pré natal e pós-parto. Métodos: Trata-se de um estudo metodológico de avaliação de usabilidade do aplicativo. A avaliação da usabilidade foi realizada com 14 enfermeiros, utilizando a escala System Usability Scale (SUS), seguindo a norma ISO/IEC 25010:2011. Resultados: O aplicativo CIPE-APS obteve escores positivos quanto a usabilidade, sendo classificado como Melhor imaginável (57%), Excelente (29%) e Bom (14%) pelos participantes da pesquisa. Conclusões: O aplicativo CIPE-APS apresentou escores altos na escala SUS,a garantir informações a consulta de enfermagem e ao processo saúde-doença compreendido no ciclo gravídico puerperal.
Usability evaluation of the CIPE-APS app in prenatal and postpartum consultations
Keywords: Mobile apps; Nursing informatics; Postpartum period; Prenatal care; Aplicativos móveis; Informática em enfermagem; Cuidado pré-natal; Período pós-parto